Association between nutrients intake and coronary heart disease among adults in Saudi Arabia: a case-control study - Aljefree, Najlaa; Shatwan, Israa; Almoraie, Noha (Progress in Nutrition, 2021)
Background and Objective: Coronary heart disease (CHD) is a leading cause of mortality worldwide. Increasing evidence links CHD to the dietary intake among different populations. This paper aims to examine the association between nutrients intake and CHD in Saudi Arabia. Methods and Study Design: A case-control study was conducted in western Saudi Arabia. An interview-administered questionnaire was performed to collect data on socio-demographic characteristics and family histories of the disease. All participants completed three consecutive daily food records. Fasting blood samples were collected to measure glucose and total cholesterol. Body weight, height, and blood pressure measurements were also recorded. Results: A total of 85 patients were included in this study. Case participants had significantly higher intakes of monounsaturated fatty acids and polyunsaturated fatty acids but lower intakes of total energy, saturated fatty acids, and trans fatty acids than did controls. In addition, case participants consumed significantly fewer carbohydrates and less calcium, sodium, and zinc than did controls. The excess intake of total energy, trans fatty acid, and sodium associated with an increased risk of CHD. Also, deficient intake of polyunsaturated fatty acids, protein, zinc, vitamin A, vitamin C, and alpha-linolenic acid associated with an increased risk of CHD among participants. Conclusions: The current study’s findings provide appropriate nutritional solutions to prevent and control the incidence of CHD in Saudi Arabia. Further studies with larger sample size are essential to confirm these findings.